Stochastic Optical Reconstruction Microscopy (STORM). Issue 1 (5th July 2017) - Xu, Jianquan; Ma, Hongqiang; Liu, Yang
Abstract: Super‐resolution (SR) fluorescence microscopy, a class of optical microscopy techniques at a spatial resolution below the diffraction limit, has revolutionized the way we study biology, as recognized by the Nobel Prize in Chemistry in 2014. Stochastic optical reconstruction microscopy (STORM), a widely used SR technique, is based on the principle of single molecule localization. STORM routinely achieves a spatial resolution of 20 to 30 nm, a ten‐fold improvement compared to conventional optical microscopy. Among all SR techniques, STORM offers a high spatial resolution with simple optical instrumentation and standard organic fluorescent dyes, but it is also prone to image artifacts and degraded image resolution due to improper sample preparation or imaging conditions. It requires careful optimization of all three aspects—sample preparation, image acquisition, and image reconstruction—to ensure a high‐quality STORM image, which will be extensively discussed in this unit. © 2017 by John Wiley & Sons, Inc.